Student Management STAI Rakha Amuntai Student Tasks Based on Library Research and Public Field Research - Dewi Yanti; Syahrani (Indonesian Journal of Education (INJOE), 2022)
Lecturers should be able to see their profession as a calling from the soul, so that they carry out their duties which are summarized in the tridharma of higher education. On the other hand, lecturers must be able to develop the talents of their students if they look talented and instill skills in their students if the skills are not visible. For this reason, STAI lecturer Rakha Amuntai began to improve by making all his student assignments more qualified by increasing the standard of assignments that were initially only papers based on published literature research, especially if there were students who were ready to make field research-based articles into published articles